2007
DOI: 10.1007/s00221-007-1001-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of finger tracking combined with electrical stimulation on brain reorganization and hand function in subjects with stroke

Abstract: Synergism of rehabilitative interventions could maximize recovery following stroke. We examined whether the combination of peripherally initiated electrical stimulation of finger extensors and centrally operating finger tracking training could accentuate brain reorganization and its relationship to recovery, beyond the effects of either treatment alone. Twenty subjects with stroke were randomly assigned to an electrical stimulation (ES), tracking training (TR) or combination (CM) group. Each group was trained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 69 publications
0
71
0
6
Order By: Relevance
“…Previous studies 3,5,7,8 have demonstrated that electrical stimulation combined with volitional efforts or additional therapy is more effective than electrical stimulation alone in the recovery process. Bhatt et al 21 showed that combined intervention may have a more beneficial influence on brain reorganization than either treatment alone. Increased motor cortical excitability facilitates greater voluntary activation of its neuronal networks, 22 which could lead to improved functions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies 3,5,7,8 have demonstrated that electrical stimulation combined with volitional efforts or additional therapy is more effective than electrical stimulation alone in the recovery process. Bhatt et al 21 showed that combined intervention may have a more beneficial influence on brain reorganization than either treatment alone. Increased motor cortical excitability facilitates greater voluntary activation of its neuronal networks, 22 which could lead to improved functions.…”
Section: Discussionmentioning
confidence: 99%
“…Vicarious recruitment of alternate ipsilesional (Dancause and others 2006; Frost and others 2003; Plow [nee (Bhatt)] and others 2007; Seitz and others 1998; Ward and others 2007; Weiller and others 1992) and contralesional (Bestmann and others 2010; Johansen-Berg and others 2002; Lotze and others 2012) motor regions and changes in their connectivity with ipsilesional PMA or with M1 can be studied with resting state fMRI. Based on correlated cortical activity in resting state, resting state fMRI defines functional connectivity between regions.…”
Section: Testing the Hypothesis In Clinical Investigationsmentioning
confidence: 99%
“…By contrast, the combination of a motor task (swallowing) with functional electrical stimulation (PES) was ineffective. Earlier research regarding hand and leg rehabilitation using motor training with sensory stimulation suggested that that this type of combined stimuli can induce larger changes in excitability and/or neuroplasticity in motor cortex [39][40][41] , whereas tongue protrusion motor training, which alone produces measured neuroplasticity and successful performance, was less effective on motor cortex with nociceptive sensory stimulation. 42 These may be due to the differences in the neural systems between spinal and cranial nerves or in the type of experimental noxious stimulus.…”
Section: Changes In the Corticobulbar Neural Circuitmentioning
confidence: 99%